Risk factors for elbow pain in Little League baseball players: a cross-sectional study focusing on developmental factors - Yukutake, T.; Nagai, K.; Yamada, M.; Aoyama, T. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: The incidence of Little League elbow is increasing. However, the risk factors for Little League elbow, especially those related to development have not previously been investigated. The purpose of this study was to investigate the risk factors for elbow pain in Little League baseball players while focusing on the developmental factors.